2018
DOI: 10.1039/c8ra01527a
|View full text |Cite
|
Sign up to set email alerts
|

Study on the flammability, thermal stability and diffusivity of polyethylene nanocomposites containing few layered tungsten disulfide (WS2) functionalized with metal oxides

Abstract: In this work, exfoliated tungsten disulfide (WS2) functionalized with metal oxides as a filler of polyethylene (PE) was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…Comparable results were obtained by a different study that undertook extracellular synthesis of silver and gold nanoparticles by employing single-cell protein (Spirulina platensis) [69]. Nanoparticles expanded in size as the reaction time was increased, whilst also showing greater aggregation and greater instability [70]. Another study synthesized various metallic nanoparticles with a range of microorganism species and observed that yield increased in direct proportion with reaction time increase [71].…”
Section: Timementioning
confidence: 91%
“…Comparable results were obtained by a different study that undertook extracellular synthesis of silver and gold nanoparticles by employing single-cell protein (Spirulina platensis) [69]. Nanoparticles expanded in size as the reaction time was increased, whilst also showing greater aggregation and greater instability [70]. Another study synthesized various metallic nanoparticles with a range of microorganism species and observed that yield increased in direct proportion with reaction time increase [71].…”
Section: Timementioning
confidence: 91%
“…This effect can be due to the thermal stability of filler and the barrier effect of these nanomaterials, which leads to the resistance of the nanocomposite to thermal degradation and prevents the penetration of degradation products from the polymer matrix to the gas phase. Several studies have been carried out on the effects of these nanomaterials on the thermal stability of various polymers [61,70].…”
Section: Application Of Graphene-like Nanocompositementioning
confidence: 99%
“…WS 2 is one of the most commonly used compounds in semiconductor TMS's. In recent years, materials such as WS 2 have attracted increased attention in the field of nanocomposite fillers, due to their high thermal and mechanical properties [69,92]. Díez-Pascual et al prepared an inorganic fullerene-like tungsten disulfide (IF-WS 2 ) lubricant, and then used this to manufacture PPS/IF-WS 2 /CF laminates via melt-blending and hot-press processing.…”
Section: Gas Phase Free Radical Inhibitionmentioning
confidence: 99%
“…Wenelska et al reported WS 2 functionalized with metal oxides (iron oxide and nickel oxide) as a filler for PEs. is showed that composites can provide a certain physical barrier and inhibit the diffusion of heat and gaseous products during combustion [69].…”
Section: Gas Phase Free Radical Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation